Die Poesie der Dinge Ziele und Strategien der Wissensvermittlung im lateinischen Lehrgedicht der Frühen Neuzeit - Markevičiūtė, Ramunė; Roling, Bernd (Frühe Neuzeit, 2021)
Distillation flasks, sugar cane mills, and the brain - the scientific revolution created a spectacular range of themes, even in a traditional genre such as didactic poetry. In this volume, internationally renowned researchers in Latin didactic poetry examine the many facets of early modern scientific poetry and offer insights on these previously neglected texts.